Tinjauan Kasasi Mahmakah Agung Atas Dasar Tidak Diterapkannya Hukum Sebagaimana Mestinya Oleh Judex Factie Dalam Perkara Tindak Pidana Korupsi - Fairuza Irfany (Sebelas Maret University, 2017)
Corruption is a problem that needs to be addressed seriously and is a legal issue in every country in the world, including Indonesia. Disease is increasingly rampant corruption. The government's seriousness in tackling corruption, namely the establishment of Law No. 31 of 1999 as amended by Act No. 20 of 2001 on Corruption Eradication. This type of research that the authors used in preparing this legal research is research doctrinal law, therefore use case approach (case approach) that is carried out by way of review of cases relating to issues that face which has become a court decision which has had the power fixed. Legal materials analysis techniques used by the author is to use legal reasoning by deduction. Issues raised are granting an appeal by the Supreme Court on the grounds Judex factie not apply the law properly in corruption. The defendant unlawfully enrich themselves or another person or a corporation that could harm the state finance and economy, conducted by Muhammad Said Madiu a way to misuse of money at. Trading Company Indonesia (PPI) Branch Gorontalo done by billing without SPP documents and invoices, but by making their own receipts, causing losses to the state amounting to Rp516.495.000,00 (five hundred and sixteen million four hundred and ninety-five thousand rupiah ). The conclusion of this study explained that the granting of an appeal by the Supreme Court is in conformity with Article 256 of the Criminal Procedure Code, namely when the Supreme Court granted the request for cassation, the Supreme Court overturned the verdict of the court filed an appeal. This study explains that the basic decision-making Supreme Court judges who change the High Court Gorontalo Number: 06 / PID.SUS.TIPIKOR / 2014 / PT.Gtlo compliance with applicable laws and regulations. Supreme Court Decision No. 1818 K / Pid.Sus / 2014 imposing sanctions of imprisonment and fines were appropriate and proper because it contains elements of a good decision. Keywords: Supreme Court of Cassation granting , Judex factie Not Implementing Law , Corruption.